Combining reverse-transcription multiplex PCR and microfluidic electrophoresis to simultaneously detect seven mosquito-transmitted zoonotic encephalomyelitis viruses. (June 2016) - Wang, Yu; Ostlund, Eileen N.; Jun, Yang; Nie, Fu-ping; Li, Ying-guo; Johnson, Donna J.; Lin, Rui; Li, Zheng-guo
Highlights: An assay combing 7-plex RT-PCR and microfluidic electrophoresis was developed. The utilization of mosquito 18S rRNA for the internal control was verified. Reliable viral genomic RNAs proved the specificity of the assay. Novel svRNA standards were used to evaluate the sensitivity of the assay. Abstract: Several mosquito-transmitted viruses are causative agents for zoonotic encephalomyelitis. Rapid identification of these viruses in mosquito populations is an effective method for surveying these diseases. To detect multiple mosquito-transmitted viral agents, including West Nile virus, Saint Louis encephalitis virus, Venezuelan equine encephalomyelitis virus, Western equine encephalomyelitis virus, Eastern equine encephalomyelitis virus, Highlands J virus and Japanese encephalitis virus, an assay using multiplex reverse-transcription PCR combined with microfluidic electrophoresis was developed and evaluated. Tailed nested primers were used in the assay to amplify specific viral genomic segments, and products with specific length were further analyzed by using a microfluidic electrophoresis chip. The assay exhibited good specificity and analytical sensitivity (10 2 copies/µL). This technology can be helpful in the quarantine and surveillance of exotic encephalomyelitis viruses which are transmitted by mosquitoes.